La vulnérabilité de la forêt provençale face aux incendies : naissance d’une notion (fin XIXe siècle) - Martine Chalvet (VertigO)
In the nineteenth century, the word vulnerability, when applied to forest, did not exist yet. Nevertheless, the notion of vulnerability to fire of the Provence forests was in the making. At the time, a new economic and technical context of the exploitation of cork and pine resin was emerging, and the paper clarifies why and how fires were regarded from then on as “disasters”. This new perception paved the way for the creation of interest pressure groups led by Charles de Ribbe and Henri Faré. They lobbied in order to obtain the elaboration and implementation of public policies and the recognition of a regional specificity of the Maures and the Esterel ranges, which were called “the region of fires” at the time. In the liberal and scientific context of the late nineteenth century, what was the meaning of vulnerability ? Who shaped this new discourse ? What types of policies and regulations were proposed ? Were they successful ?